Electrooxidation of polar benzotriazole - The impact of supporting electrolyte - Helena Prosen; Borislav N. Malinović; Eva Korenčić; Jernej Markelj; Stefan Vranješ; Tijana Đuričić (Journal of Chemists, Technologists and Environmentalists, 2020)
Polar benzotriazoles are heterocyclic compounds widely used in industry, and as such are easily released into the environment. These compounds show harmful and toxic effects on plants and some aquatic organisms, biodegrade quite slowly, and some, depending on the structure, have the ability to bioaccumulate. They can only be partially removed by conventional wastewater treatment, and are therefore found in a variety of waters, as well as solid waste. In this paper, synthetic wastewater containing polar benzotriazole was treated by an electrooxidation process. The efficiency of the treatment was tested depending on various parameters, such as: anode material (mixed metal oxide - MMO and boron-doped diamond - BDD), applied current density (10 and 20 mA/cm2), type of supporting electrolyte (NaCl, Na2CO3, Na2SO4, H2SO4) and treatment time (0.5 - 2.5 h). Obtained results showed the treatment was more effective at higher current density and by using BDD anode. Also, the efficiency of the treatment increases with the prolongation of the electrolysis time. After 2.5 h of treatment, 97.9% of benzotriazole was removed, in the presence of sulfuric acid as supporting electrolyte.